Factors influencing COVID-19 testing among Native Americans and Latinos in two rural agricultural communities: a qualitative study - Van Rensburg, Dillon; Adams, Alexandra K.; Perez, Georgina; Bishop, Sonia; Warne, Teresa; Hassell, Laurie; Quigley, Thomas; Garza, Lorenzo; Dupuis, Virgil; Drain, Paul K.; Whiting Sorrell, Anna; Ko, Linda K. (Frontiers in Public Health, 2023)
Objective. To examine factors influencing decisions to test for COVID-19 among Native Americans on the Flathead Reservation in Montana and the Latino community in the Yakima Valley of Washington state. Methods. We conducted 30 key informant interviews with community leaders and six focus groups with community members to examine factors impacting decisions to test for COVID-19 during the second year of the COVID-19 pandemic from May 2021 to June 2021. Results. Three major themes that impacted testing for COVID-19 were identified: (1) Social factors, including the influence of families and friends and employment practices; (2) health factors, including testing procedures, home-based testing, and health communication; and (3) contextual factors, including distrust for government and medical communities and the impact on cultural practices and celebrations. Conclusions. Social, health, and contextual factors influence the decision to test for COVID-19. Understanding the community’s perception is critical for successful implementation of preventive strategies.